2019
DOI: 10.4081/jphia.2019.1180
|View full text |Cite
|
Sign up to set email alerts
|

The independence of pregnant women in early detection of high risk of pregnancy in terms of parity, knowledge and information exposure

Abstract: The ability of pregnant women to detect early of a high risk pregnancy is still below the average which is one of the causes of complications that can endanger the wellbeing of the mother and fetus. The purpose of this study is to determine the relationship between factors of parity, knowledge and exposure to information on the independence of mothers in early detection of the risk of pregnancy. This type of analytic observational research uses a cross sectional design. A total sample of 125 pregnant women was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
1
15
0
1
Order By: Relevance
“…The analysis found that women who get more exposed to media had better knowledge. This finding is in line with the findings of other previous studies, which confirm that media exposure is the best tool for increasing knowledge [4]. Meanwhile, another study in Indonesia about the effects of the Maternal and Child Health Handbook on improving knowledge of the pregnancy danger signs found contradictory results.…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…The analysis found that women who get more exposed to media had better knowledge. This finding is in line with the findings of other previous studies, which confirm that media exposure is the best tool for increasing knowledge [4]. Meanwhile, another study in Indonesia about the effects of the Maternal and Child Health Handbook on improving knowledge of the pregnancy danger signs found contradictory results.…”
Section: Plos Onesupporting
confidence: 90%
“…In general, better knowledge of the pregnancy danger signs is one of the determinants of early pregnancy detection [4]. Vigilance against the pregnancy danger signs is one of the right strategies to reduce the maternal mortality [11].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…In complex or diverse family and cultural environments. In fact the role of husband and family also influences pregnant women in supporting the behavior or actions of pregnant women in utilizing health services (Mardiyanti, Nursalam, Devy, & Ernawati, 2019a). A person's health behavior is determined, among others, by the presence or absence of support from the surrounding community (social support) (Baron et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Increased understanding of pregnancy danger symptoms, which has a high association with early diagnosis of pregnancy hazards, can help prevent conception. Women who understand the pregnancy hazard symptoms are 6.657 times more likely to discover pregnancy concerns early than those who do not [4]. Antenatal care is strongly linked to knowledge of pregnancy hazard symptoms [3].…”
Section: Introductionmentioning
confidence: 99%